Exploring Students’ Creative Thinking Process in Solving Triangle Problems Assisted by GeoGebra - Wahyu Kartikawati; Tatag Yuli Eko Siswono (Journal of Mathematical Pedagogy (JoMP), 2024)
The study aims to describe student’s creative thinking process in solving triangle problems using GeoGebra. This qualitative approach involved six students selected from 28 students in grade 8 based on the case categories of student’s abilities namely high mathematical abilities (HMA), medium mathematical abilities (MMA), and low mathematical abilities (LMA). Data collection techniques were conducted through mathematical ability tests (MAT) to determine research subjects, creative thinking tests assisted by GeoGebra to determine students’ creative thinking processes, and interviews. The data analysis technique uses indicators of creative thinking stages according to Siswono, and data reduction from interviews to explore student’s creative thinking processes. The research results show that student’s creative thinking processes at the stages of synthesizing ideas, generating ideas, planning the implementation of ideas, and implementing ideas have different processes at each ability level. At the stage of synthesizing ideas, all students synthesize their ideas by combining the knowledge they have, both from everyday life and during classroom learning. All students were able to mention the information contained in the questions. LMA had difficulty relating the information in the questions to daily life and learning experiences in class, but HMA and MMA were able to relate it smoothly. At the idea-building stage, HMA and MMA can come up with two ideas for solutions using GeoGebra, while LMA can only come up with one idea. At the stage of planning to implement the idea, HMA and MMA had other ideas for solving the problem, but LMA only had one idea for solving it. At the stage of applying ideas, HMA and MMA can show two different answer ideas, while LMA can only show one answer idea. HMA was able to solve questions using GeoGebra smoothly, but MMA and LMA were less fluent, all subjects checked their answers again, HMA and MMA were confident in their answers, but LMA was less confident in their answers.